2020
DOI: 10.21203/rs.2.20425/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices (KAP) of Diabetics towards Diabetes and Diabetic Retinopathy in Riyadh, Saudi Arabia: Cross-sectional study

Abstract: Objective : To identify the knowledge, attitude, and practices (KAP) of diabetic patients towards diabetes and diabetic retinopathy in Riyadh, Saudi Arabia. Methods: This cross sectional study was conducted in 50 randomly selected primary care centers and two university hospitals in Riyadh, Saudi Arabia, between May and December 2018. Diabetic patients ≥ 18 years old were enrolled in the study. A validated KAP-45 questionnaire was used to assess the KAP levels of diabetics towards diabetes and diabetic retinop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…25 Nevertheless, the median knowledge score of participants in this study was 6 and more than 62% toward the poor tier. The median knowledge score for diabetes was 10 (good knowledge range 9–17), according to Al-Yahya et al 18 The average knowledge score for DM was good among our participants, which is comparable with another research performed in Fiji by Zibran et al, who found a good level of knowledge with a mean knowledge score of 23.3 out of 30 (SD 3.25). 26 In India, on the other hand, John et al found that 58% of their sample lacked good knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…25 Nevertheless, the median knowledge score of participants in this study was 6 and more than 62% toward the poor tier. The median knowledge score for diabetes was 10 (good knowledge range 9–17), according to Al-Yahya et al 18 The average knowledge score for DM was good among our participants, which is comparable with another research performed in Fiji by Zibran et al, who found a good level of knowledge with a mean knowledge score of 23.3 out of 30 (SD 3.25). 26 In India, on the other hand, John et al found that 58% of their sample lacked good knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…The questionnaire used for this study was prepared based on previous studies published in a similar context as well as including additional questions based on local diabetic attitudes and practices that were deemed relevant. [16][17][18] The questionnaire is composed of 2 sets, the first of which focuses on the patient's demographics, such as age, gender, employment position, educational attainment, and smoking habits. The second section of the questionnaire was devoted to questions about KAP (knowledge, attitude, and practice).…”
Section: Design Of the Questionnairementioning
confidence: 99%
“…Based on the age group (Table 1 and Fig. 1), there were 17 patients in between 25-35 years, 63 patients between 36-45 years, 115 patients between 56-65 years and 43 patients between 66-75 years and majority of the patients were in the age group of 46-55 years (n=124) which was similar to the study carried out by Abdurrahman Al-Yahiya at al., 2020 [18]. Based on the gender (Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%